Comparison Between Sonography-Based and Surgical Evaluation of Endometriotic Lesions Using the #Enzian Classification – A Retrospective Data Analysis - Di Giovanni, Alessandra; Montanari, Eliana; Hudelist, Gernot; Malzoni, Mario; Keckstein, Joerg (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Purpose To compare the location and sizes of deep endometriosis (DE) lesions evaluated by preoperative transvaginal sonography (TVS) in different #Enzian compartments with intraoperatively assessed DE location and size.Materials and Methods Retrospective data analysis of 93 women undergoing TVS and surgery for DE in 2019 at a tertiary referral center for endometriosis.Results #Enzian compartment C (rectum) showed the highest rate of exact concordance with 74% of cases, which increased to 87% when a tolerance margin of a maximum of 3mm for TVS measurements was taken into account. For compartment B (uterosacral ligaments, parametria) and compartment A (vagina, rectovaginal space), the rates of exact concordance were slightly lower. In compartment O (ovary), high exact concordance rates similar to those observed for compartment C were observed. In compartment T (tubo-ovarian unit), most reliable estimations were seen for slight (TVS T1) and severe adhesions (TVS T3). There were only a few cases of missed lesions as well as false positives on TVS: Sensitivity was 100% for all compartments except for A and B left (97%) and FB (urinary bladder, 86%); specificity was 100% for FB, FI (other intestinal locations), FU (ureters) and O right, 86%-98% for A, B right, C, O left and FO (other extragenital lesions) and 70% for B left.Conclusion The preoperative evaluation of the location and size of DE lesions by TVS in different #Enzian compartments is accurate, providing a detailed presurgical description of the extent of ovarian and deep endometriosis and associated minor or severe adhesions.
Keywords: lesion size; preoperative evaluation; #Enzian classification; transvaginal sonography (TVS); THEMES; surgery